(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2008)
The algorithm and qualifiers for identification of sound signals is offered. The work of qualifiers illustrated on an example of recognition of sounds “a”, “o” and “y”.